2005
DOI: 10.1103/physrevb.72.075418
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity landscape of highly oriented pyrolytic graphite surfaces containing ribbons and edges

Abstract: We present an extensive study on electrical spectroscopy of graphene ribbons and edges of highly oriented pyrolytic graphite (HOPG) using atomic force microscope (AFM). We have addressed in the present study two main issues, (1) How does the electrical property of the graphite (graphene) sheet change when the graphite layer is displaced by shear forces? and (2) How does the electrical property of the graphite sheet change across a step edge? While addressing these two issues we observed, (1) variation of condu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 19 publications
6
68
0
1
Order By: Relevance
“…In the literature, the edges of graphene sheets from highly oriented pyrolitic graphite have been directly investigated by scanning tunneling microscopy (STM) in association with scanning tunneling spectroscopy (STS) [129 132] and by direct contact atomic force microscopy (AFM) [133,134]. Micro-Raman spectroscopy has also proved to be a valuable tool for studying the armchair or zigzag orientation of the ribbon edges locally [135].…”
Section: Nano Researchmentioning
confidence: 99%
“…In the literature, the edges of graphene sheets from highly oriented pyrolitic graphite have been directly investigated by scanning tunneling microscopy (STM) in association with scanning tunneling spectroscopy (STS) [129 132] and by direct contact atomic force microscopy (AFM) [133,134]. Micro-Raman spectroscopy has also proved to be a valuable tool for studying the armchair or zigzag orientation of the ribbon edges locally [135].…”
Section: Nano Researchmentioning
confidence: 99%
“…40,41 As shown in Figure 3e, the surface presents several graphitic planes that show distinct electrical conductivity, in agreement with the behavior previously reported employing metal-coated AFM probes for its characterization. [40][41][42][43] We found that a single tip could be used for more than 50 hours for conductive AFM measurements without noticeable deterioration in performance (a total of > 50 images, each of a 5 ”m × 5 ”m area). Our transfer method brings to the fore a quick and easy approach for making these tips.…”
mentioning
confidence: 92%
“…Graphite mainly exists in hexagonal form, but the rhombohedral form can also exist together with the hexagonal structure [4]. Stacking faults in the crystal can act as breaks in the conduction paths along the c-axis direction, which can lead to accumulation of charges [24,25]. These accumulated charges can lead to built-in electric potentials in the crystal.…”
Section: Edge-plane Surface Illuminationmentioning
confidence: 99%